2023
DOI: 10.1109/access.2023.3272482
|View full text |Cite
|
Sign up to set email alerts
|

DeepCurvMRI: Deep Convolutional Curvelet Transform-Based MRI Approach for Early Detection of Alzheimer’s Disease

Abstract: Alzheimer's Disease (AD) is the most common form of dementia. It usually manifests through progressive loss of cognitive function and memory, subsequently impairing the person's ability to live without assistance and causing a tremendous impact on the affected individuals and society. Currently, AD diagnosis relies on cognitive tests, blood tests, behavior assessments, brain imaging, and medical history analysis. However, these procedures are subjective and inconsistent, making an accurate prediction for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…In the result analysis, the model achieved 83%, 81%, and 85% precision for healthy, mild, and severe AD. C. M. Chabib et al [22] suggested a DeepCurvMRI model that combined a CNN and the Curvelet Transform (CT) to improve the accuracy of early-stage AD identification using MRI scans. After pre-processing the MRI images with CT, these modified images were used to train the CNN model.…”
Section: A Analysis Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…In the result analysis, the model achieved 83%, 81%, and 85% precision for healthy, mild, and severe AD. C. M. Chabib et al [22] suggested a DeepCurvMRI model that combined a CNN and the Curvelet Transform (CT) to improve the accuracy of early-stage AD identification using MRI scans. After pre-processing the MRI images with CT, these modified images were used to train the CNN model.…”
Section: A Analysis Of Admentioning
confidence: 99%
“…Meanwhile, ADNI [1], [45], [47], and the Open Access Series of Imaging Studies (OASIS) [36], [37] stand out as significant contributors to advancing research in this domain. Structural MRI [2], [18], [27], [32], [33], [36], [39] OASIS MRI MRI images with a focus on brain tumor detection Structural MRI [5], [8], [14], [15], [17], [19], [21], [22], [24], [25], [36], [37], [38], [42], [43] MRI ADNI Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset Functional and Structural MRI, PET [1], [4], [4], [7], [16], [23], [28], [29], [30], [40], [41], [44], [45] ADNI GARD Gwangju Alzheimer's and Related Dementia (GARD) dataset…”
Section: Figure 5 Ad Detection Using Various Technique Modelsmentioning
confidence: 99%
“…First, the MRI pictures were preprocessed using CT, and then the CNN model was trained using this new representation of the data. DeepCurvMRI [38] was trained on the Alzheimer's MRI images dataset that is accessible on the Kaggle platform for both binary and multi-class classification tasks.…”
Section: Graph Reasoning Module (Grm) Formentioning
confidence: 99%
“…Recently, researchers have focused on two main approaches for training and classifying models, conventional learning and deep learning, as they proved excellent in other domains [ 28 , 29 , 30 ]. Recent studies like [ 24 , 31 , 32 , 33 , 34 ] used conventional learning for AD classification, while studies like [ 5 , 35 , 36 , 37 , 38 ] employed deep learning techniques.…”
Section: Related Workmentioning
confidence: 99%
“…The Kaggle ADNI version dataset was used by Chabib et al [ 38 ] to employ curvelet transform (CT) based on the CNN model to determine early-stage AD detection. They first used CT for pre-processing, then a CNN model was trained to utilize it for new image representation.…”
Section: Related Workmentioning
confidence: 99%